Managerial accounting - Moore, Carl L.; Jaedicke, Robert K. (Dallas, South-western Pub. Co., 1967)
"Managerial Accounting's objective is to explain how accounting data can be interpreted and used by the management in planning and controlling business activities. For the most part, business problems are discussed from the point of view of internal management. Although the major purpose of this book is to show how accounting can help to solve the problems that confront those who are directly responsible for the management of the enterprise, the use of accounting data by investors and potential investors is also discussed whenever appropriate. The book is divided into four basic parts. In part I the basic financial statements are discussed. The subject matter of Part II is the interpretation of the interrelationships of financial data. These two parts are given first because a student should understand the basic financial relationship, the limitations of financial data, and how to analyze data before he can intelligently use financial information. Parts III and IV show how information developed in accounting systems can be in planning and controlling business activities and in making business decisions. "
Includes index.
English text.
Keywords: Managerial accounting; Cost accounting